Cytokine, chemokine, and acute-phase protein profiles in plasma as correlative biomarkers of clinical outcomes for patients with COVID-19 - Sierra G. Vanderkamp; Maysa Niazy; Ashley A. Stegelmeier; Kevin J. Stinson; Nicole Ricker; Byram W. Bridle (Scientific Reports)
Abstract Coronavirus disease identified in 2019 (COVID-19), caused by severe acute respiratory syndrome-coronavirus-2, had a global impact on human health and the economy. The aim of this study was to quantify cytokines, chemokines, and acute phase proteins in the plasma of patients with COVID-19 to elucidate potential biomarkers to inform prognostic and treatment decisions. Clustering analysis using the K-prototypes method identified underlying biological patterns in patients with COVID-19. The penalized multinomial logistic regression analysis identified two comorbidities (hypertension, congestive heart failure) and thirteen analytes as potential risk factors for COVID-19 progression with 88.2% accuracy. Based on a patient’s age, high concentrations of interleukin (IL)-6, monocyte chemoattractant protein-1, and pentraxin 3 were important biomarkers for lethal COVID-19. Decreased concentrations of interferon gamma-induced protein-10, IL-10, and soluble tumor necrosis factor receptor I were found to be associated with mild COVID-19, while increasing concentrations of these analytes could be used to predict COVID-19 severity.